2014
DOI: 10.4161/cbt.29188
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Database

Abstract: Pancreatic cancer is the fourth leading cause of cancer-related death in the world. The etiology of pancreatic cancer is heterogeneous with a wide range of alterations that have already been reported at the level of the genome, transcriptome, and proteome. The past decade has witnessed a large number of experimental studies using high-throughput technology platforms to identify genes whose expression at the transcript or protein levels is altered in pancreatic cancer. Based on expression studies, a number of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…In addition, in our series a small panel of 5 overexpressed PDAC markers (S100A11, GPR137B, SULF1, POSTN and miR-155) would allow precise distinction between PDAC and non-tumoral pancreatic tissues. In line with this hypothesis, strong expression of the S100A11 and GPR137B genes has been reported at the protein level in PDAC tissues, while SULF1 and POSTN are expressed at more variable patterns [ 67 - 69 ]; of note all four proteins have been also found to be secreted and present in both tumor tissues and the plasma [ 67 , 68 , 70 ] from PDAC patients. Altogether, secretion of these proteins outside the tumor cell, supports the potential utility of these genes as candidate markers for the diagnosis and monitoring of PDAC patients.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, in our series a small panel of 5 overexpressed PDAC markers (S100A11, GPR137B, SULF1, POSTN and miR-155) would allow precise distinction between PDAC and non-tumoral pancreatic tissues. In line with this hypothesis, strong expression of the S100A11 and GPR137B genes has been reported at the protein level in PDAC tissues, while SULF1 and POSTN are expressed at more variable patterns [ 67 - 69 ]; of note all four proteins have been also found to be secreted and present in both tumor tissues and the plasma [ 67 , 68 , 70 ] from PDAC patients. Altogether, secretion of these proteins outside the tumor cell, supports the potential utility of these genes as candidate markers for the diagnosis and monitoring of PDAC patients.…”
Section: Discussionmentioning
confidence: 84%
“…But until now no studies have focused on these 3 TFs in IPMN. Moreover, most of the regulated genes (18/25) of these three TFs could be found in Pancreatic Cancer Database [ 41 ]. Nevertheless, our study indicates that these three TFs may be the key regulators in early stage of IPMN and are definitely worth further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of a number of microRNAs is also altered in pancreatic cancer and its precursors, and again, it has been suggested that these alterations could form the basis for the early detection of pancreatic neoplasia 2426 . All of these changes in gene expression ultimately are associated with changes in protein expression, and these alterations in protein expression can form a foundation for a rational basis for chemoprevention and early detection 27 .…”
Section: Keynote Speaker Ralph Hruban: Biology Of Pancreatic Cancermentioning
confidence: 99%